1991
DOI: 10.1520/jfs13093j
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Use of Laser-Induced Infrared Luminescence to Differentiate Writing Inks

Abstract: An examination of 56 inks with an argon-ion laser revealed the laser will sometimes stimulate infrared luminescence in inks which did not produce infrared luminescence under the video spectral comparator (VSC-1). This infrared luminescence was always at a higher range (usually 830 to 900 nm) than that found under the VSC-1. This indicates that laser-induced infrared luminescence may be a useful tool in differentiating between inks which otherwise appear similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Capillary zone electrophoresis has been applied to the analysis of water-soluble fiber-tip pen inks from documents (774) . An examination of 56 inks with an argon ion laser revealed that laser-induced IR luminescence may be a useful tool in differentiating inks (775). Colored pencils have been differentiated by TLC (776).…”
Section: Forensic Biochemistrymentioning
confidence: 99%
“…Capillary zone electrophoresis has been applied to the analysis of water-soluble fiber-tip pen inks from documents (774) . An examination of 56 inks with an argon ion laser revealed that laser-induced IR luminescence may be a useful tool in differentiating inks (775). Colored pencils have been differentiated by TLC (776).…”
Section: Forensic Biochemistrymentioning
confidence: 99%
“…In the initial studies on ink dating research [ 1 , 12 , 13 ], static approaches such as ink stroke measurement (size, color, hue, value, and chroma according to international notation and light reflectance) were used to differentiate inks. Other analytical methods such as ultraviolet-visible (UV-Vis) spectrometry [ 14 ], infrared luminescence spectrometry [ 15 ], near infrared-UV-Vis (NIR-UV-Vis) spectrometry [ 16 ], video spectral comparator [ 17 ], laser-induced fluorescence [ 13 ], and laser-induced infrared luminescence [ 18 ] were also applied to compare and identify inks. Ink analysis based on the extraction rate obtained using solvents with different polarities against a sufficiently expansive database of reference samples was also widely adopted as a relative ink dating method.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques that are used by Forensic Document Examiners (FDEs) to detect these types of forgery are based on physical, microscopic and chemical examination [2], [3], [4], [5], [6], [7]. Some modern imaging tools are also available but those are not at all automatic.…”
Section: Introductionmentioning
confidence: 99%